Investigation of helium plasma stream parameters in experiments on surface modification - Bandura, A.N.; Byrka, O.V.; Chebotarev, V.V.; Garkusha, I.E.; Ladygina, M.S.; Marchenko, A.K.; Tereshin, V.I.; Trubchaninov, S.A.; Tsarenko, A.V. (Вопросы атомной науки и техники, 2005)
Processing of different constructional materials with pulsed plasma streams is one of prospective methods of surface modification. The main objection of this study is adjustment of plasma treatment regimes for different materials that allows achieving optimal thickness of modified layer with simultaneously minimal value of surface roughness. With use of optical spectroscopy, detailed information about the basic plasma parameters – electron density, electron and ion temperatures, plasma stream duration and velocity, was obtained. Integrated spectra of plasma radiation were analyzed. The majority of helium and impurity spectral lines were investigated on a subject of Stark broadening. Plasma pressure and energy density values measured with piezodetectors and calorimeters are in good agreement with plasma parameters obtained by optical techniques. Один з перспективних методів модифікації поверхні – це обробка різних конструкційніх матеріалів імпульсними плазмовими потоками. Головна ціль досліджень є оптимізація режимів плазмової обробки різних матеріалів, що одночасно дозволяє досягати оптимальної товщини модифікованого шару та мінімальної величини шорсткості поверхні. Детальна інформація про основні параметри плазми – електронна густина, електронна та іонна температури, тривалість та швидкість плазмового потоку, була отримана за допомогою оптичної діагностики. Проаналізовані інтегральні спектри випромінювання плазми. Більшість гелієвих та домішкових спектральних ліній досліджувались на предмет Штарківського розширення. П`єзодатчиками та калориметрами виміряні величини тиску та густини енергії плазми, які добре погоджуються з параметрами плазми, отриманими за допомогою оптичної діагностики. Одним из перспективных методов модификации поверхности является обработка различных конструкционных материалов импульсными плазменными потоками. Главная цель этой работы – оптимизация режимов плазменной обработки для различных материалов, что одновременно позволяет достигать максимальной толщины модифицированного слоя и минимальной величины шероховатости поверхности. Детальная информация об основных плазменных параметрах – электронная плотность, электронная и ионная температуры, длительность генерации и скорость плазменного потока, была получена с помощью оптической диагностики. Проанализированы интегральные спектры излучения плазмы. Большинство гелиевых и примесных спектральных линий исследовались на предмет Штарковского уширения. Пьезодатчиками и калориметрами измерены соответственно величины давления и плотности энергии плазмы, которые хорошо согласуются с параметрами плазмы, полученными с помощью оптической диагностики.